Chapter The pressures and the ecological quality status of the Marmara Sea (Turkey) by using marine macroalgae and angiosperms - Taskin, Ergün (Proceedings e report, 2020)
In the present study, the Marine Floristic Ecological Index (MARFEI) was tested to assess the impacts by using marine benthic macrophytes and pressures by using the Macroalgae-Land Uses Simplified Index (MA-LUSI) in the Marmara Sea (Turkey). Sampling of benthic macrophytes was made from 0-5 m depth at 29 different sites during the summer periods of 2017, 2018 and 2019. The study revealed good ecological status class (ESC) for 6 sites, moderate for 11 sites, poor for 8 sites and bad for 4 sites. MARFEIeqr showed a negative linear relationship with the pressure index MA-LUSI.